Late Cretaceous species of Vologesia (Echinoidea, Cassiduloida) from northern Spain - Schlüter, Nils; Wiese, Frank (Zootaxa, 2017)
A new species of the echinolampadid genus Vologesia, V. rollingstones sp. nov., is recorded from the lower Campanian of northern Cantabria (Spain). Additionally, material of Vologesia toucasi, of late Santonian age, is described from the same area; this species had previously been noted only for southern France.